High-density lipoprotein from subjects with coronary artery disease promotes macrophage foam cell formation: role of scavenger receptor CD36 and ERK/MAPK signaling - Sini, S.; Deepa, D.; Harikrishnan, S.; Jayakumari, N. (Molecular and cellular biochemistry, 2017)
Although high-density lipoprotein is atheroprotective, it can become dysfunctional in chronic inflammatory conditions and increase cardiovascular risk. We previously demonstrated that HDL from subjects with documented coronary artery disease is dysfunctional and is pro-oxidant/proinflammatory in macrophages. Here we examined the influence of dysfunctional/proinflammatory HDL (piHDL) on lipid accumulation in human macrophages, in comparison to functional HDL (nHDL). Exposure of macrophages to piHDL, in contrast to nHDL, resulted in oxidative stress and marked uptake of lipids from piHDL, leading to the formation of foam cell phenotype as noted by oil red O staining with concomitant increase in total cellular cholesterol content. Using western blotting, we identified that piHDL profoundly upregulated the expression of scavenger receptor CD36 and suppressed the expression of ABCG1 and SRB1 in macrophages, thereby facilitating cholesterol influx capacity of macrophages. We then identified that CD36 did not act alone, indeed it was activated in macrophages along with ERK/MAPK, in response to piHDL, which in turn led to lipid accumulation as well as proinflammatory response via activation of NFkB and subsequent release of proinflammatory markers—TNF-ά and MMP-9. These effects were confirmed using pharmacological inhibitors for either CD36 or ERK/MAPK. Furthermore, piHDL treatment moderately activated PPAR-γ and Nrf2, the known regulators of CD36 in macrophages, suggesting that the two forms of HDL differentially regulate CD36 expression. Taken together, the results demonstrate that a novel CD36-ERK/MAPK-dependent mechanism is involved in macrophage lipid accumulation by piHDL, there by revealing the importance of functional deficiency in HDL and its potential link to atherogenesis.